The role of interpersonal communication in education = Rola komunikacji interpresonalnej w edukacji - Famuła-Jurczak, Anita; Gejdos, Miroslav; Kobiałka, Andrzej (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The rapid pace of changes occurring in our society causes that we are increasingly faced with the question: what should be the aim of education? Finding the answer is di?cult as the multiplicity and variety of factors that a?ect the development of the personality of our pupils is such that it is impossible to predict what impact they may have on the functioning of individuals. Given social changes taking place, the issue of a crisis in education is frequently raised. The aim of this paper is to show the importance of interpersonal communication in creating the educational process.
Keywords: communication; education; komunikacja; edukacja